Cannabinoids and the endocannabinoid system in liver diseases - Anna Parfieniuk-Kowerda; Diana Martonik; Aleksandra Andrzejuk; Aleksander Tarasik; Robert Flisiak (Clinical & Experimental Hepatology)
Cannabinoids are biologically active substances acting via feedback-coupled CB1 and CB2 receptors. Their expression in myofibroblasts and liver endothelial cells is reported to be elevated in chronic liver diseases. The effect of CB1 receptor stimulation is to increase fibrosis and inflammatory activity in the liver by stimulating stellate cells, while activation of the CB2 receptor results in inhibition of fibrosis. Stimulation of the CB1 receptor may also lead to progression of liver steatosis and carcinogenesis. In end-stage liver disease, the endocannabinoid system plays an important role in the pathogenesis of encephalopathy and vascular effects, such as portal hypertension, splanchnic vasodilatation and cirrhotic cardiomyopathy. It seems that interference in endocannabinoid transmission may serve as an attractive target for the development of hepatological drugs.